Confirmatory factor analysis of autism and schizophrenia spectrum traits. (1st May 2017) - Ford, Talitha C.; Apputhurai, Pragalathan; Meyer, Denny; Crewther, David P.
Abstract: The relationship between the Autism Spectrum Quotient (AQ) and Schizotypal Personality Questionnaire (SPQ) data has consistently shown overlap in the social and interpersonal domains. Factor analyses of the AQ and SPQ subscales support this overlap with the emergence of a shared AQ and SPQ subscale factor as the largest common element. This study investigated, at the item level, the factor structure of the AQ and SPQ. Exploratory and confirmatory factor analyses were conducted on the AQ and SPQ responses of 1670 participants (aged 18–40, 1243 females, 427 males). Seven factors cumulatively explained 40.56% of the data. Of these, four represented shared traits (named Odd Behaviour, Relationship Disinterest, Cue Interpretation, Social and Communication Discomfort), one was a more specific autistic tendency (named Fixation with Details), and two factors were more specific to the psychotic dimension of schizotypy (named Paranoia/Suspiciousness and Hallucination/Delusional Experiences). These findings demonstrate that a set of symptom traits is present in both the autism and schizophrenia spectra. The findings of this study have important clinical implications in terms of future research, diagnosis and treatment of autism and schizophrenia spectrum disorders. Highlights: Autistic and schizotypal personality traits are found to overlap to a large degree. Four personality traits are identified as 'shared' in the autism and schizotypal spectra. Two personality traits are specific to the schizotypal spectrum. One personality trait is specific to the autism spectrum. 31/124 items are sufficient to classify the 7 autistic and schizotypal personality traits.